FUTURE TRANSLATORS' INDEPENDENT WORK IMPROVING ON THE BASIS OF THE USA EXPERIENCE - Natalia Bidyuk; Alyona Nakonechna (Vasyl Stefanyk Precarpathian National University, 2018)
The article deals with the directions of improving the organization of independent work of students-translators on the basis of studying American experience. In the course of the research various models of professional competence of the translator were analyzed. They got acquainted with conducting the translation business in the USA and programs for its realization with the help of a computer, namely the so-called SAT technologies. An equally important component of the learning environment for students is the human resource, that is, the teacher as a teacher, an assistant accompanying the student in the process of his independent work. That is why, it is expedient to organize the independent work of students-translators in order to focus on the formation of student autonomy and the ability to self-education throughout their professional life. Key words: students-translators, education, USA, independent work.